Enhancing Efficiency Performance Measurement of Zakat Institutions: - Tjahjani, Fera; Masruki, Rosnia; Ibrahim, Norhazlina (Journal of Accounting, Business and Management (JABM), 2025)
Law Number 23 of 2011 concerning the management of zakat mandates that the Badan Amil Zakat Nasional (BAZNAS) and Lembaga Amil Zakat (LAZ) must manage zakat funds efficiently and effectively. BAZNAS currently utilises four types of ratios to measure efficiency performance separately: (1) collection expenses ratio, (2) operational expenses ratio, (3) human resource expenses ratio, (4) amil fund ratio. However, most of studies related to efficiency performance assessment of zakat institutions use the Data Envelopment Analysis (DEA) index. The DEA index measures efficiency by comparing the amount of output and input, but its input and output components are flexible, depending on the researcher’s perspective, and it does not explicitly incorporate the 12.5% amil rights. This study aims to propose a new index to measure efficiency performance in a more appropriate and integrated manner, referring to Indonesian Financial Accounting Standard (IFAS) 401, the DEA index, and the amil fund ratio. This proposed index is expected to be more accurately assess the efficiency performance of zakat institutions